CURRENT AQUACULTURE AND FISHERY ACTIVITIES AT THUY TRIEU LAGOON, CAM LAM, KHANH HOA PROVINCE - Thuy, Nguyen Thi Thanh; Hoa, Nguyen Xuan; Thuy, Nguyen Nhat Nhu (Vietnam Journal of Marine Science and Technology, 2014)
The surveyed results showed that the aquaculture and inshore fishery activities at Thuy Trieu lagoon have developed privately and spontaneously; the total area of unused ponds was up to 68.94%; 100% of shrimp farmers and fishermen have not participated any fishery associations. So far, there has no a specific plan for aquaculture at the lagoon; 60% of farming ponds is nearby industrial wastewater; 43.33% of farming ponds is nearby agricultural wastewater and 30% of farming ponds is nearby residential wastewater, in which 20% of the farming ponds is nearby both industrial and residential wastewater. The infrastructure for aquaculture has not been invested by the local budgets:the electrical and freshwater systems have been only invested by the shrimp farmers; pathways at the concentrated aquaculture areas have not been extended and cemented; 86.67% of farming ponds without wastewater treatment system; 53.33% of farming ponds without inlet and outlet systems separately. The aquaculture and inshore fishery have not sustainably developed: 46.67% of shrimp farmers have tended to reduce aquaculture areas in the coming years; 46.67% of the fishermen have tended to change their occupation; 86.67% of shrimp farmers asserted that the profit decreases significantly compared to that of 5 years ago. The marine recourses in the lagoon decrease significantly compared to those of 5 years ago. There have no local specific regulations in management, sanctions as well as supporting policies for the aquaculture and inshore fishery at Thuy Trieu lagoon.